Experimental Investigation on Mechanical Properties of Hybrid Steel and Polyethylene Fiber-Reinforced No-Slump High-Strength Concrete - Tian-Feng Yuan; Jin-Young Lee; Kyung-Hwan Min; Young-Soo Yoon (International Journal of Polymer Science)
This paper presents experimental investigations on the mechanical properties of no-slump high-strength concrete (NSHSC), such as the compressive and flexural strength. First, to determine the proper NSHSC mixtures, the compressive and flexural strength of three different water-to-binder ratios (w/b) of specimens with and without polyethylene (PE) fiber was tested at test ages. Then, the effect of hybrid combinations of PE fiber and steel fiber (SF) on the compressive strength, flexural strength, flexural toughness, and flexural energy dissipation capacity was experimentally investigated. Furthermore, the various hybrid fiber-reinforced NSHSCs were evaluated, and their synergy was calculated, after deriving the benefits from each of the individual fibers to exhibit a synergetic response. The test results indicate that a w/b of 16.8% with or without fibers had lower strength and flexural strength (toughness) than those of other mixtures (w/b of 16.4% and 17.2%). Specimens with a hybrid of SF and short PE fibers exhibited a higher compressive and flexural strength, flexural toughness, energy dissipation capacity, and fiber synergy in all considered instances.